THE EFFECT OF DISCIPLINE AND MOTIVATION ON EMPLOYEE EFFECTIVENESS AT SEBERIDA SUBDISTRICT OFFICE INDRAGIRI HULU DISTRICT (JURNAL MANAJEMEN DAN BISNIS, 2021)
This study aims to examine and analyze the effect of discipline and motivation on the work effectiveness of employees at the Seberida Subdistrict Office, Indragiri Hulu Regency. The sample used in this study were all 35 employees of the sub-district office using the census method. data analysis using multiple linear regression. The results of the study showdiscipline variables and variablesmotivation has a significant effect on the employee's work effectiveness variable. While the discipline variable has a significant effect on the employee's work effectiveness variable and the motivation variable has no significant effect on the employee's work effectiveness variable.